2021
DOI: 10.3390/molecules26195983
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antipoliferative Activities of Novel Substituted Imidazole-Thione Linked Benzotriazole Derivatives

Abstract: A new series of benzotriazole moiety bearing substituted imidazol-2-thiones at N1 has been designed, synthesized and evaluated for in vitro anticancer activity against the different cancer cell lines MCF-7(breast cancer), HL-60 (Human promyelocytic leukemia), and HCT-116 (colon cancer). Most of the benzotriazole analogues exhibited promising antiproliferative activity against tested cancer cell lines. Among all the synthesized compounds, BI9 showed potent activity against the cancer cell lines such as MCF-7, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Anticancer activity screening results revealed that compound 48 was the most promising anticancer agent having IC 50 values of 3.57, 0.4, 2.63 and 118.9 µM, respectively. CA-4 was used as a reference drug with IC 50 values of 0.58, 0.77, 0.24, and 13.6 µM, respectively[ 165 ]. Quinazoline-based imidazole derivatives were synthesized and screened for their anticancer activity against epidermal growth factor receptor (EGFR) and HT-29 cell lines (normoxic and hypoxic conditions) by Kumar et al (2022).…”
Section: Current Advances In Nitrogen Containing Heterocycles As Anti...mentioning
confidence: 99%
“…Anticancer activity screening results revealed that compound 48 was the most promising anticancer agent having IC 50 values of 3.57, 0.4, 2.63 and 118.9 µM, respectively. CA-4 was used as a reference drug with IC 50 values of 0.58, 0.77, 0.24, and 13.6 µM, respectively[ 165 ]. Quinazoline-based imidazole derivatives were synthesized and screened for their anticancer activity against epidermal growth factor receptor (EGFR) and HT-29 cell lines (normoxic and hypoxic conditions) by Kumar et al (2022).…”
Section: Current Advances In Nitrogen Containing Heterocycles As Anti...mentioning
confidence: 99%
“…Benzotriazole exhibiting different pharmacological activities. [21][22][23][24][25][26][27][28] Year Benzotriazole derivative synthesized Authors/Investigator Reported activity Ref.…”
Section: High-performance Thin-layer Chromatography (Hptlc) Studiesmentioning
confidence: 99%
“…Moreover, azetidine-2-one structural moiety has almost recognized as therapeutic potential. [20] Benzotriazole and its Pharmacological Activity [21][22][23][24][25][26][27][28] Also act as strong vasodilator, hypotensive, antibacterial, antifungal, and antiparasitic properties were demonstrated by benzofuran derivatives. [29] Different nitrogen-containing spiroheterocyclic derivatives were isolated from natural sources and prepared synthetically such as from frog neurotoxin example histrionicotoxin 283 A, shelf fish toxins includes spirolides etc.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the 3,4,5‐trimethoxyphenyl ring of CA‐4 could be adequately replaced by the substituted benzotriazole ring. [ 48 ]…”
Section: Benzotriazoles As Anticancer Agentsmentioning
confidence: 99%